2021
DOI: 10.1016/j.jneuroim.2021.577629
|View full text |Cite
|
Sign up to set email alerts
|

New-onset refractory status epilepticus following the ChAdOx1 nCoV-19 vaccine

Abstract: Coronavirus is a novel human pathogen causing fulminant respiratory syndrome (COVID-19). Developing an effective and reliable vaccine was emergently pursued to control the dramatic spread of the global pandemic. The standard stages for vaccine development were unprecedentedly accelerated over a few months. We report a case of new-onset refractory status epilepticus (NORSE) after receiving the first dose of the ChAdOx1 nCoV-19 vaccine. We attribute the occurrence of NORSE to the vaccine due to the temporal rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 11 publications
0
41
0
4
Order By: Relevance
“…Fear of seizure worsening, and concerns about the adverse effects and efficacy rank among the leading causes of vaccination hesitancy. Cases of seizure onset after COVID-19 vaccination [31] , [39] , [40] might influence the clinicians’ decision to recommend vaccination in patients with epilepsy. However, our analysis showed that epilepsy related problems after COVID-19 vaccination such as increased seizure frequency and status epilepticus were uncommon in most of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of seizure worsening, and concerns about the adverse effects and efficacy rank among the leading causes of vaccination hesitancy. Cases of seizure onset after COVID-19 vaccination [31] , [39] , [40] might influence the clinicians’ decision to recommend vaccination in patients with epilepsy. However, our analysis showed that epilepsy related problems after COVID-19 vaccination such as increased seizure frequency and status epilepticus were uncommon in most of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the generalised convulsions have proven to be associated with immunization, seizures following the ChAdOx1 nCoV-19 vaccine are rarely reported. [19][20][21] Two other hospitalized patients with high-grade fever and severe body aches made a complete recovery with symptomatic treatment and were discharged after a short period of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Los autores de esta publicación teorizan que, al ingresar al SNC, el vector viral de la vacuna podría haber inducido una cascada inflamatoria con la consecuente epileptogénesis, simulando uno de los mecanismos por los que la infección por SARS-CoV-2 produce clínica neurológica. 43…”
Section: Norse Y Covid-19unclassified